2022
DOI: 10.3390/cells11020276
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Normoxic and Hypoxic U-87 Glioblastoma Paracrine Secretion on the Modulation of Brain Endothelial Cells

Abstract: Background: Glioblastoma multiforme (GBM) is a highly invasive brain tumour, characterized by its ability to secrete factors promoting its virulence. Brain endothelial cells (BECs) in the GBM environment are physiologically modulated. The present study investigated the modulatory effects of normoxically and hypoxically induced glioblastoma U-87 cell secretions on BECs. Methods: Conditioned media (CM) were derived by cultivating U-87 cells under hypoxic incubation (5% O2) and normoxic incubation (21% O2). Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…For the first assumption, we found controversial data. While a previous study showed that puromycin-purified rat BMECs culture exhibited improved barrier properties, including TEER values (Calabria et al, 2006 ), several works also demonstrated that BMECs co-cultured with pericytes and astrocytes might enhance the conditions of the primary culture system (Abbott, 2002 ; Siddharthan et al, 2007 ; Wisniewska-Kruk et al, 2012 ; Jamieson et al, 2019 ; Rado et al, 2022 ). On the other hand, cell culture seeding density impact the viability and suitability of the cell culture over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first assumption, we found controversial data. While a previous study showed that puromycin-purified rat BMECs culture exhibited improved barrier properties, including TEER values (Calabria et al, 2006 ), several works also demonstrated that BMECs co-cultured with pericytes and astrocytes might enhance the conditions of the primary culture system (Abbott, 2002 ; Siddharthan et al, 2007 ; Wisniewska-Kruk et al, 2012 ; Jamieson et al, 2019 ; Rado et al, 2022 ). On the other hand, cell culture seeding density impact the viability and suitability of the cell culture over time.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclei are stained with DAPI (blue), N = , Scale bar µm. -Kruk et al, 2012;Jamieson et al, 2019;Rado et al, 2022). On the other hand, cell culture seeding density impact the viability and suitability of the cell culture over time.…”
Section: DIVmentioning
confidence: 99%
“…This chemical property justi es the term 'protonophore', as positively charged protons characterized by their hydrophilic nature, typically require channels, transporters, or passive diffusion facilitated by protonophores to traverse membranes [28,29]. Prominent examples of protonophores are compounds like CCCP, 2,4-dinitrophenol, or triphenylphosphonium, which are known for their cytotoxic potential in various cancer cell types, including breast cancer, lung cancer, neuroblastoma, and glioblastoma cells [30][31][32]. These agents function by disrupting the normal proton gradient across the inner mitochondrial membrane, thereby uncoupling oxidative phosphorylation (OXPHOS) and diminishing ATP production.…”
Section: Bromoxib Acts As a Mitochondrial Uncouplermentioning
confidence: 99%
“…Mitochondria are an essential regulator of cell proliferation [ 22 ]. In our previous studies [ 23 , 24 ], we showed that mitochondrial activity of endothelial cells (bEnd.3) was suppressed after cultivation with paracrine factors secreted from breast and GBM cancer cells. Mitochondria regulate cell signalling pathways, cell death and gene expression, including cell division [ 25 ].…”
Section: Introductionmentioning
confidence: 99%